FUTSAL DRIBBLING TRAINING MODEL WITH TOOLS FOR JUNIOR HIGH SCHOOL - Asep Setiawan; Iman Sulaiman; Iwan Setiawan; Rizka Antoni (Gladi : Jurnal Ilmu Keolahragaan, 2021)
The purpose of this study to produce a variety of futsal dribbling training models with effective and tested media for Junior High Schools (SMP). The research method used in this research is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model using five stages and the research subjects are three futsal extracurricular trainers in Junior High Schools (SMP). This research begins with a analysis, product planning, development, implementation and evaluation. The instruments used in this study included an assessment questionnaire for experts to test the validity of the variety of futsal dribbling training models with media tools and an assessment questionnaire to assess the effectiveness of the model by futsal extracurricular trainers in Junior High Schools (SMP). The data analysis technique used in this research is the percentage descriptive analysis technique. This study produces a variety of training models that meet the established criteria, are valid and effective. Research recommendations should be made before the dissemination of the futsal dribbling training model using the media as a tool for junior high schools (SMP) to be tried again to athletes / students to make it more effective and efficient.